Impact of multiple disturbances on coral communities at a remote shallow reef in the South China Sea - Syed Muhammed Sumayed; Chun Hong Tan; Chun Hong Tan; Nor Aieni Haji Mokhtar; Zainudin Bachok (Frontiers in Marine Science)
Coral reefs around the world are affected by numerous disturbances, such as high-intensity cyclones and severe thermal anomalies, which are occurring with increasing frequency and intensity. In 2019, our study site Pulau Bidong near Terengganu, Peninsular Malaysia, was affected by the passage of tropical storm Pabuk over this region, followed by a localized bleaching event later in the year. This study investigated the changes in reef cover and composition over a 5-year period between 2017 and 2021, before and after these successive natural disturbances. At the beginning of our study, live coral cover was 46.11 ± 7.56% and the reef was in a “fair” condition. However, after the multiple disturbances in 2019, the live coral cover decreased by 68% to 14.63 ± 4.35%, mainly due to the decline of the dominant genera Fungia sp. and Acropora sp. The coral bleaching triggered by the local heat stress event mainly affected the massive Fungia sp., as the branching Acropora sp. were severely affected by the previous storm event due to their mechanical vulnerability. After the successive disturbances, SIMPER showed that the community composition in Pulau Bidong had changed. After the disturbance, ‘dead corals covered with algae’ (DCA) now dominated the reef benthos, whereas previously live corals (Fungia sp.) dominated the reef picture. The nMDS plot showed a clear clustering of the benthic community composition between years, with the disturbance survey transects clustered separately from the years without disturbance. The β-diversity box plot showed that the reef community was rather monotonous before the disturbances, but after the consecutive disturbances in 2019, there was a higher variation in coral diversity. Although Pulau Bidong experienced multiple disturbances, the community structure recovered somewhat to pre-disturbance levels towards the end of our study in 2021.